Intercostal nerve cryoablation therapy for the repair of pectus excavatum: a systematic review - Eldredge, R. Scott; McMahon, Lisa (Frontiers in Surgery, 2023)
Introduction: The minimally invasive repair of pectus excavatum is a painful procedure that can result in long hospitalization and opioid use. To mitigate the length of stay and opioid consumption many different analgesia strategies have been implemented. The aim of this study was to review the use and patient outcomes of intercostal nerve cryoablation (INC) during pectus excavatum repair reported in the literature. Methods: An unfunded, literature search using PUBMED identifying articles discussing INC during pectus excavatum repair between 1946 – April 21, 2023. Articles were included if they discussed patient outcomes with INC use during pectus excavatum repair. Articles were excluded if they were reviews/meta-analyses, editorials, or not available in English. Each article was reviewed for bias by analyzing study methods, data analysis, patient selection, and patient follow up. Articles comparing outcomes of INC were considered significant if p-value <0.05. Results: A total of 34 articles were included in this review which described INC during pectus repair. Most supported a decreased hospital length of stay and opioid use with INC. Overall INC was associated with fewer short-term and long-term complications. Researchers reported mixed total hospital costs with the use of INC. Conclusion: The reviewed was limited by a paucity of prospective studies and low number of patients who received INC. Despite this the current data supports INC as a safe effective analgesic strategy during the repair of pectus excavatum.